Ipsilateral fasciocutaneous flaps for leg and foot defects - Bhattacharya, Visweswar; Watts, Rajesh Kumar (Indian Journal of Plastic Surgery, 2003)
It was a revolutionary enhancement for lower limb reconstruction when fasciocutaneous flaps were first described and used in clinical practice in 1981. Subsequently persistent studies were made to emphasize and confirm the rich vasculai net'"voik associated with deep iascia. Thereafter studies were directed to identify the various types of perforators supplying the deep fascia and the overlying subcutaneous tissue and skin. Accordingly the scientists classified these flaps keeping in mind theii clinical applications. The authors of this articie have aiso performed extensive research on various aspects. This has led to better understanding about the finer details of vascularity. Based on this various modifications have been made for safe application of reconstruction for defects extending from knee to sole. To avoid complications the clinician should be able to select the proper procedure as regards the donor site and the possible preoperative and postoperative technical faults. A well-designed and meticulously executed flap usually has smooth recovery. Both Colour Doppler and Audio Doppler are useful tools in planning a safe flap. Now these flaps have proved to be standard technique without requiring a special set up extensive training.
Keywords: Fasciocutaneous flaps; Antegrade flaps; Retrograde flaps; Defects of leg and foot; Doppler studies; Perforator based flaps